Dementia in Fragile X-Associated Tremor/Ataxia Syndrome (FXTAS): Comparison with Alzheimer’s Disease - Seritan, Andreea L. (2008)
BACKGROUND: Neurocognitive deficits in fragile X-associated tremor/ataxia syndrome (FXTAS) involve attentional control, working memory, executive functioning, and declarative and procedural learning. To date, no studies comparing FXTAS with other dementias have been done. We characterize the dementia in FXTAS, comparing it with Alzheimer’s disease. METHODS: Retrospective chart review of 68 adults (50 men, 18 women) with FXTAS. 20 men with FXTAS dementia were matched by age, gender, and education to patients with mild Alzheimer's dementia (AD). Neuropsychological measures were compared between the two groups: Boston Naming Test (BNT), phonemic fluency (Controlled Oral Word Association Test), digit span forward (DSF) and backward (DSB). Comparisons were based on analysis of covariance and t-tests to assess significant differences between groups with respect to the neuropsychological measures. RESULTS: 50% of men with FXTAS and no women were cognitively impaired. On mean scores of verbal fluency (22.83 in FXTAS vs. 28.83 in AD, p = 0.112), working memory (DSB, 4.80 in AD vs. 5.41 in FXTAS, p = 0.359), and language (BNT, 48.54 in AD vs. 54.20 in FXTAS, p = 0.089), there were no significant differences. Digit span forward, measuring attention, was significantly higher in subjects with FXTAS dementia (8.59, vs. 7.10 in AD, p = 0.010). CONCLUSION: Individuals with FXTAS have significant cognitive deficits, on the order of those in AD although the cognitive profiles in these dementias are not similar. Further research is needed to outline the neuropsychiatric profile in FXTAS and the correlation of genetic markers with the progression and severity of cognitive loss.